2020
DOI: 10.1093/eurheartj/ehaa293
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and weight loss are inversely related to mortality and cardiovascular outcome in prediabetes and type 2 diabetes: data from the ORIGIN trial

Abstract: Aims The association of body weight and weight change with mortality and cardiovascular (CV) outcome in patients with diabetes mellitus (DM) is not clearly established. We assessed the relationship between weight, weight change, and outcomes in patients with established CV risk factors and type 2 DM or pre-diabetes. Methods and results A total of 12 521 participants from the ORIGIN trial were grouped in BMI categories of low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 30 publications
(35 reference statements)
7
59
1
Order By: Relevance
“…In contrast to the impact of new-onset AF, our study demonstrated that neither baseline BMI nor BW loss after SGLT2i treatment affected the risk of MACE/HF hospitalization in patients with T2DM treated with SGLT2i. This finding agreed with a recent analysis reporting that sustained BW loss was not associated with a lower risk of MACE/HF hospitalization among 12,521 prediabetes or T2DM participants from the ORIGIN trial [ 51 ]. The Look AHEAD trial applied a comprehensive lifestyle intervention program to overweight patients with type 2DM.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the impact of new-onset AF, our study demonstrated that neither baseline BMI nor BW loss after SGLT2i treatment affected the risk of MACE/HF hospitalization in patients with T2DM treated with SGLT2i. This finding agreed with a recent analysis reporting that sustained BW loss was not associated with a lower risk of MACE/HF hospitalization among 12,521 prediabetes or T2DM participants from the ORIGIN trial [ 51 ]. The Look AHEAD trial applied a comprehensive lifestyle intervention program to overweight patients with type 2DM.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our results, data from the ORIGIN trial showed that among participants with T2DM or prediabetes, 1-year weight gain and weight loss, respectively, were associated with decreased and increased risk of an outcome composite of the first occurrence of cardiovascular death, non-fatal myocardial infarction, or non-fatal stroke during over 6 years of follow-up [15]. In a meta-analysis of prospective studies, despite a high Table 3 Multivariable hazard ratios (HR) and 95% confidence intervals (CI) of association between weight change categories and incident CHD: Tehran Lipid and Glucose Study, Iran, 1999-2018 Model 1: adjusted for age and sex.…”
Section: Discussionsupporting
confidence: 89%
“…Results of the recent studies on this issue also remained inconsistent. Data from the ORIGIN trial and the Anglo-Danish-Dutch Study of Intensive Treatment in People with Screen-Detected Diabetes in Primary Care (ADDITION)-Cambridge trial showed significant protection for weight loss among participants with T2DM [14,15]; however, the Action in Diabetes and Vascular disease: preterAx and diamicroN-MR Controlled Evaluation (ADVANCE) trial showed a significantly increased risk of CVD among participants with weight loss [16]. Moreover, results from other studies were not statistically significant for the association of weight loss with CVD [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown in patients with DM or with prediabetes and a wider range of cardiovascular comorbidity 7,8 that WL in these patients was associated with increased mortality. Further studies are warranted to explore why the co-morbidity of heart failure and DM seems to attenuate this effect.…”
mentioning
confidence: 98%